Biological characterization of a simian immunodeficiency virus-like retrovirus (HTLV-IV): evidence for CD4-associated molecules required for infection. - Hoxie, J A (1988)
We have analyzed a number of biological features of HTLV-IV, a retrovirus indistinguishable from a macaque isolate of simian immunodeficiency virus (SIV), and compared this virus with several strains of human immunodeficiency virus type 1 (HIV-1). Although HTLV-IV was found to be similar to HIV-1 in its tropism for CD4+ lymphocytes, its effects on CD4 expression and the ability of its externalized envelope molecule to form a complex directly with the CD4 molecule, a number of striking differences were noted. Unlike with HIV-1, the range of cells susceptible to HTLV-IV infection and syncytia formation was restricted to a subset of CD4+ cell lines, particularly those that coexpressed CD4 with human leukocyte antigen (HLA) class II antigens. An analysis of the patterns of HTLV-IV infection with B x T somatic cell hybrids indicated that for this virus, molecules in addition to CD4 were probably required to facilitate infection and cell fusion. Additional studies of HTLV-IV infection of Sup-T1 cells, which are exquisitely sensitive to cytopathic effects induced by HIV-1, demonstrated that HTLV-IV infection could occur in the absence of cytopathic effects and, remarkably, with minimal or no downmodulation of the CD4 molecule from the cell surface. The failure of HTLV-IV infection to reduce the expression of several CD4 epitopes suggested that the HTLV-IV envelope produced by Sup-T1 cells was altered in its ability to interact with or bind to CD4. Additional differences were also noted in the size of the transmembrane envelope molecule of HTLV-IV produced by Sup-T1 cells, indicating that cell-specific alterations in processing of the HTLV-IV envelope occurred during the production of virus in this cell line. Understanding the basis for these biological differences between HTLV-IV and the HIV-1 viruses may help to elucidate more general mechanisms for pathogenesis of other members of the SIV and HIV families of retroviruses.